The Oxford Handbook of Human Motivation 2012
DOI: 10.1093/oxfordhb/9780195399820.013.0024
|View full text |Cite
|
Sign up to set email alerts
|

Effort Intensity: Some Insights From the Cardiovascular System

Abstract: This chapter deals with the psychological process that determines effort intensity in instrumental behavior. According to motivation intensity theory, effort should be proportional to experienced task difficulty as long as success is possible and justified and low when success is impossible or excessively difficult, given the available benefit. When task difficulty is unspecified or unknown, effort should be proportional to the importance of success. We report a program of experimental studies that have operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
193
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(209 citation statements)
references
References 47 publications
15
193
1
Order By: Relevance
“…Alternatively, physiological arousal levels are known to vary as a function of the difficulty level of a task or, in other words, the amount of cognitive effort that is needed to perform a task [31]. Previous research has demonstrated that physiological indicators such as heart rate [32,33], skin conductance [34,35] and systolic blood pressure [35][36][37] can be used as indicators of the amount of effort one mobilizes to perform a task.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, physiological arousal levels are known to vary as a function of the difficulty level of a task or, in other words, the amount of cognitive effort that is needed to perform a task [31]. Previous research has demonstrated that physiological indicators such as heart rate [32,33], skin conductance [34,35] and systolic blood pressure [35][36][37] can be used as indicators of the amount of effort one mobilizes to perform a task.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In other words, if a task is too difficult or impossible to perform, effort falls and remains low (see Wright [38] for an overview). It is not yet clear which physiological indicator of arousal is the most valid predictor of mobilized effort during cognitive task performance (see Gendolla et al [31]), but most evidence has been found for systolic blood pressure [31,37,39,40]. This is hypothesized to be the case because systolic blood pressure is largely determined by sympathetic beta-adrenergic activity, which has been found to increase during effortful task performance [38].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Taken together, PEP can be considered a reliable means for operationalizing effort mobilization (Kelsey, 2012;Wright, 1996). SBP qualifies as a secondary measures of effort mobilization that has been successfully used in the framework of motivational intensity theory, whereas the evidence for DBP and HR is mixed (for reviews see Gendolla, Brinkmann, et al, 2012;Gendolla, Wright, et al, 2012).…”
Section: Effort Mobilization and Cardiovascular Responsementioning
confidence: 99%
“…As noted above, DBP strongly depends on vascular resistance and therefore does not qualify as a reliable indicator of beta-adrenergic sympathetic activation. In line with these physiological considerations, evidence for DBP effects in the research on motivational intensity theory has been mixed (Gendolla, Brinkmann, et al, 2012;Gendolla, Wright, et al, 2012).…”
Section: Interpretation Of Cardiovascular Response Patternsmentioning
confidence: 99%
“…A more promising measure of effort mobilization is the pre-ejection period (PEP) (Gendolla, Wright, & Richter, 2012;Kelsey, 2012;Richter, Friedrich, & Gendolla, 2008). PEP is defined as the period between the onset of left ventricular contraction and aortic valve opening (Weissler, 1977) and has been considered to be a useful indicator of the contractile state of the heart (Kelsey, 2012;Sherwood et al, 1990).…”
Section: Introductionmentioning
confidence: 99%